PENGARUH KONTROL DIRI TERHADAP PERILAKU PENGENDARA TRANSPORTASI ANGKUTAN BARANG DI KOTA MAKASSAR - Harun, A. Muh. Yusuf; Pertiwi, Nurlita; Ali, M. Ichsan (UNM Environmental Journals, 2023)
The development of an area or region depends on the mobility of transportation facilities and infrastructure. This development is related to the increase in population and activities. These goods transport vehicles are also an indicator of the progress of an area which also drives the economic activities of its people. This research aims to see the magnitude of the influence of self-control in driving goods transportation. This research uses a quantitative descriptive type of research carried out in the Maminasata area which covers the Makassar City area, Regency. Takalar, Parts of Maros Regency and Parts of Gowa Regency. The results of the research show that the driver's self-control is in the moderate category or means that the driver is able to control himself while driving, such as controlling the speed and arranging the travel route to utilize travel time.